Blood Pressure Factors on Proteinuria in Type 2 Diabetes Mellitus Patients - Putra, Muhamad Dwi; Suryanda, Faradillah; Utami, Ikrimah Nisa; Harlyana, Cyntya (Muhammadiyah Medical Journal, 2023)
Background: Diabetes mellitus (DM), one of the metabolic degenerative diseases, requires significant resources to treat complications. Microvascular complications are diabetic nephropathy which is characterized by proteinuria. Blood pressure monitoring is part of self-management to avoid complications. Purposes: This study aims to determine the relationship between blood pressure and proteinuria in patients with type 2 diabetes mellitus at the Matraman District Health Center, East Jakarta. Methods: This study used a cross-sectional study analysis by collecting secondary data on patients diagnosed with type 2 diabetes mellitus at the Matraman District Health Center, East Jakarta for the period Juli-October 2021. Results: A total of 51 patients were sampled in this study; 34 (66.7%) were female and 17 other patients (33.3%) were male. Most cases with an age range of 45-64 years, namely 38 patients (74.5%). On examination of blood pressure with the highest frequency, 27 patients (52.9%) had normal blood pressure; on examination of proteinuria, found proteinuria +1 in 25 patients (49%), proteinuria +2 in 3 patients (5.9%), and proteinuria negative as many as 23 patients (45,1%). From the results of the Gamma correlation obtained a value (p= 0.022) (r = 0.441). Conclusion: Based on the results of this study, in patients with type 2 diabetes mellitus, the highest age range was 45-64 years, with more cases found in women, normal blood pressure, and +1 proteinuria levels. A significant relationship exists between blood pressure and proteinuria in type 2 diabetes mellitus patients at the Matraman District Health Center, East Jakarta.